2016
DOI: 10.2147/dddt.s96581
|View full text |Cite
|
Sign up to set email alerts
|

Saussurea tridactyla Sch. Bip.-derived polysaccharides and flavones reduce oxidative damage in ultraviolet B-irradiated HaCaT cells via a p38MAPK-independent mechanism

Abstract: ObjectiveTo investigate whether Saussurea tridactyla Sch. Bip.-derived polysaccharides and flavones exert apoptosis-inhibiting effects in ultraviolet B (UVB)-irradiated HaCaT cells.MethodsWe divided HaCaT cells into low radiation UVB and high radiation UVB groups. Low radiation UVB and high radiation UVB groups were further divided into a control group, UVB radiation group (UVB group), S. tridactyla Sch. Bip.-derived polysaccharides and flavones low-dose group, and S. tridactyla Sch. Bip.-derived polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…After blocking with 5% nonfat milk or 2% BSA, the membrane was incubated with primary antibodies at 4°C overnight (phospho-STAT3 Ab, AF3293, Affinity Biosciences; STAT3 Ab AF6294, Affinity Biosciences) with actin as a loading control and then incubated at room temperature with HRP-conjugated secondary antibodies for 1 hr in the dark. The signal was developed with ECL Reagent (Beyotime) according to the manufacturer's directions and imaged with a chemiluminescent imaging system ChemiDoc (Bio-Rad) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After blocking with 5% nonfat milk or 2% BSA, the membrane was incubated with primary antibodies at 4°C overnight (phospho-STAT3 Ab, AF3293, Affinity Biosciences; STAT3 Ab AF6294, Affinity Biosciences) with actin as a loading control and then incubated at room temperature with HRP-conjugated secondary antibodies for 1 hr in the dark. The signal was developed with ECL Reagent (Beyotime) according to the manufacturer's directions and imaged with a chemiluminescent imaging system ChemiDoc (Bio-Rad) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The signal was developed with ECL Reagent (Beyotime) according to the manufacturer's directions and imaged with a chemiluminescent imaging system ChemiDoc (Bio-Rad) [26].…”
Section: Western Blotmentioning
confidence: 99%
“…In the current study, high‐throughput screening of compound libraries (IMM, Institute of Material Medica) revealed that compound 4 , belonging to the flavone class, has a significant anti‐H 3 R activity (Figure ). It was the first found that flavones could inhibit H 3 R. The molecular skeleton of flavones is the preferred structure which possess hepatoprotective, anti‐inflammatory, anti‐oxidation, antibiosis, anticancer, antiviral, cardiovascular‐protective, and anticoagulation activities. To increase the flavones inhibitory activity of H 3 R, further optimization and modification based on the structure of compound 4 was conducted to develop new flavone derivatives with potent H 3 R inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed cells contain certain polysaccharides that play important roles in controlling cell division, regulating cell growth, and maintaining the normal metabolism of living organisms ( 21 ). A variety of seaweed polysaccharides have biological activities, including scavenging free radicals in vitro , protecting cells from oxidative damage, and inhibiting oxidative damage in animals ( 22 24 ). In this study, mannitol, ribose, anhydrous glucose, xylose, and fucose were found in AIMP for the first time.…”
Section: Discussionmentioning
confidence: 99%